Epidemiological study of thyroid cancer at global, regional, and national levels from 1990 to 2021: an analysis derived from the Global Burden of Disease Study 2021 - Lu Zhang; Liangliang Jiang; Rong Xu; Xuemei Zhang; Boxun Zhang; Rensong Yue (Frontiers in Endocrinology)
ObjectiveA comprehensive evaluation of the disease burden is essential for identifying effective strategies to address thyroid cancer. This study delineates the long-term global trends in thyroid cancer and its epidemiological characteristics.MethodsData on thyroid cancer from the Global Burden of Disease 2021 were utilized. The burden of thyroid cancer was assessed through measures of incidence, mortality, disability-adjusted life years (DALYs), and the socio-demographic index (SDI). Additionally, a global risk attribution analysis was conducted, and the Bayesian age-period-cohort (BAPC) model was employed to project the future global burden of thyroid cancer.ResultsIn 2021, there were an estimated 2 million (95% UI: 1.8, 2.2) cases of thyroid cancer worldwide, with an age-standardized prevalence rate of 23.1 (95% UI: 20.7, 25.6) per 100,000 individuals, reflecting a 55% increase since 1990. The global mortality from thyroid cancer in 2021 was 44,800 (95% UI: 39,900, 48,500), with an age-standardized rate of 0.5 per 100,000 people (95% UI: 0.5, 0.6), marking a 7% decrease since 1990. In the same year, the global total number of DALYs attributable to thyroid cancer was 1,246.5 thousand (95% UI: 1,094.4, 1,375.9), with an age-standardized rate of 14.6 per 100,000 population (95% UI: 12.8, 16.1), representing a 4.2% reduction compared to 1990.ConclusionOver the past three decades, the age-standardized prevalence rate of thyroid cancer has increased, while the age-standardized mortality rate and DALY rate have decreased. Significant variations in prevalence, morbidity, and mortality exist across regions and countries. SDI plays a crucial role in the development of thyroid cancer, which is expected to remain a major public health challenge in the future.